2020
DOI: 10.1002/cncy.22354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on cytology practice: An international survey in the Asia‐Pacific region

Abstract: BACKGROUND: The purpose of the current study was to examine the impact of coronavirus disease 2019 (COVID-19) on various aspects of cytology practice in the Asia-Pacific region. METHODS: An online questionnaire was distributed to cytopathology laboratories in 24 Asia-Pacific countries to explore the impact of restrictive measures on access to health care, use of general and personal protective equipment (PPE), and changes in cytology workflow and workload from February to April 2020. RESULTS: A total of 167 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…In addition, the study by Wang et al described modifications to the structures of the laboratory workforce, and changes in cytopathology specimen volumes and laboratory workflows. Similar to the study by Vigliar et al, 3 Wang et al 4 also observed a reduction in cytology specimen volumes, although to a lesser degree than in the study by Vigliar et al It remains to be seen how the COVID‐19 pandemic will affect various aspects of cytopathology laboratories as we move into 2021 among fears of a second surge in infections, but hopes are high for the development and distribution of an effective vaccine to bring some stability to the situation. In the interim, laboratories worldwide are publishing and sharing their experiences and, through a global effort, appear poised to meet the challenges that lie ahead.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…In addition, the study by Wang et al described modifications to the structures of the laboratory workforce, and changes in cytopathology specimen volumes and laboratory workflows. Similar to the study by Vigliar et al, 3 Wang et al 4 also observed a reduction in cytology specimen volumes, although to a lesser degree than in the study by Vigliar et al It remains to be seen how the COVID‐19 pandemic will affect various aspects of cytopathology laboratories as we move into 2021 among fears of a second surge in infections, but hopes are high for the development and distribution of an effective vaccine to bring some stability to the situation. In the interim, laboratories worldwide are publishing and sharing their experiences and, through a global effort, appear poised to meet the challenges that lie ahead.…”
supporting
confidence: 71%
“…This month's issue of Cancer Cytopathology includes several original articles, commentaries, and correspondence describing a wide range of topics related to the effects of the COVID‐19 pandemic on the field of cytopathology. In particular, the journal features 2 large, multi‐institution studies investigating the effects of the COVID‐19 pandemic on the function of cytopathology laboratories around the world 3,4 . Vigliar et al have presented their study describing an astounding 45.3% decrease in the number of cytology specimens during the peak of the pandemic compared with before the pandemic 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, since the beginning of the current health crisis, restrictive measures, imposed to thwart the relentless spread of COVID-19, have dramatically disrupted many health care services, not least cytopathology practices. 1,2 Although the Italian government eased safety measures on May 4, 2020, the impact of the coronavirus emergency persisted beyond the end of the lockdown. Indeed, our clinic experienced an overall workload reduction of 41.6% in the first weeks of the postlockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the pandemic has also affected cytopathology diagnostic activity [10][11][12][13][14][15][16][17][18]. Indeed, since hospitals have been advised to review all scheduled elective procedures to minimize or postpone non-urgent procedures, cytological screening activities and cytological sampling of patients at low risk of malignancy have all been postponed.…”
Section: Introductionmentioning
confidence: 99%